2013
DOI: 10.4028/www.scientific.net/kem.554-557.512
|View full text |Cite
|
Sign up to set email alerts
|

Simple Tests as Critical Indicator of Intra-Ply Shear Locking

Abstract: Standard finite elements can exhibit the numerical artifact of intra-plyshear locking during forming simulations. The displacement fields of elementsare piecewise continuous and cannot correctly capturediscontinuities in the shear field. This shear locking is illustrated insimulations of bias-extension experiments with an unaligned mesh. Two simpletests were developed as a critical indicator of intra-ply shear locking intriangular elements. A single-element-test shows the origin of the locking anda pull-out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…This mismatch between physical realistic displacement field and the interpolation field of the element leads to locking, as stated above. This can be seen in the recently developed single-element test [6]. The interelement-continuity, on the other hand, is continuous.…”
Section: Discontinuities In Composite Forming Simulationsmentioning
confidence: 92%
See 2 more Smart Citations
“…This mismatch between physical realistic displacement field and the interpolation field of the element leads to locking, as stated above. This can be seen in the recently developed single-element test [6]. The interelement-continuity, on the other hand, is continuous.…”
Section: Discontinuities In Composite Forming Simulationsmentioning
confidence: 92%
“…Several solutions have been proposed for the tension locking in fiber reinforced materials, as discussed in [6]. Ten Thije et al [4] suggested SRI as well as MF elements as solutions to intra-ply shear or tension locking.…”
Section: Lockingmentioning
confidence: 99%
See 1 more Smart Citation